Do Nondomestic Undergraduates Choose a Major Field In Order to Maximize Grade Point Averages? - Bergman, Matthew E.; Fass-Holmes, Barry (Journal of International Students, 2016)
The authors investigated whether undergraduates attending an American West Coast public university who were not U.S. citizens (nondomestic) maximized their grade point averages (GPA) through their choice of major field. Multiple regression hierarchical linear modeling analyses showed that major field’s effect size was small for these undergraduates’ academic marks in mandatory English writing classes and their term GPAs in the five most recent academic years. Engineering and economics, but not science, were significant predictors of writing marks. Economics, but not engineering or science, was a significant predictor of GPAs.